Lateral Facies Trends in Deep-Marine Slope and Basin Floor Matrix-Rich Beds, Neoproterozoic Windermere Supergroup, British Columbia, Canada - Angus, Katrina (Université d'Ottawa / University of Ottawa, 2016)
This study investigates the lithological characteristics, and lateral and vertical facies trends of poorly understood, deep-marine matrix-rich sedimentary rocks. Two laterally extensive, well-exposed outcrops of slope and proximal basin floor deposits were investigated from the Neoproterozoic Windermere Supergroup. Significantly, matrix-rich beds have been found to undergo the same lateral trends (over ~200-650 m) in both outcrops. Initially, thicker, clayey sandstone transitions laterally to a bipartite bed with the development of an upper, planar-based, more matrix-rich unit. Further laterally, the basal unit progressively thins until it pinches out, and all that remains is the upper, more matrix-rich unit – a sandy claystone. It too thins and then pinches out. Draping the entire transect is a thin, matrix-poor structured unit overlain by a mudstone or claystone cap. These trends are interpreted to reflect a progressive but rapid lateral evolution of flow structure controlled primarily by particle settling, namely sand, from mud-rich avulsion-related flows.
Keywords: matrix-rich sandstones; particle settling; bipartite beds; avulsion; slope; proximal basin floor